Synthesis, Chemical Characterization, and Bacterial Inhibition Studying of New Mixed Ligand Complexes of 4-Methylimidazoleazo Ligand, and Ethylenediamine with Some Divalent Metal Ions - Israa N. Witwit, Hawraa M.Farhan (Pakistan Journal of Medical & Health Sciences, 2022)
New synthesized series of mixed ligand complex prepared for Co (II), Ni (II), Cu (II), Cd (II), and Hg (II) ions, with azo compound derived from 4-methylimidazole as a primary ligand (TBPAM) , and ethylene diamine as a secondary ligand. Mass , 1HNMR, C.H.N, Uv-Vis, FT-IR, Atomic Absorption, Molar Conductivity, and Magnetic Susceptibility techniques were used to characterize the complexes, the results were indicated the octahedral geometry with a general formula [M(TBPAM)(en) Cl2] for all complexes, where primary and secondary ligands behaved as a bidentate, finally a noticeable bacterial inhibition of the complexes and primary ligand at a concentration (100mg/ml) was appeared against complexes against Klebsiella, P.aeruginosa, and S. aureus bacteria Keywords: Mixed ligand; Complexes, Biological investigation; imidazole; ethylenediamine.